A touch of code : interactive installations and experiences. - Feireiss, Lukas; Feireiss, Lukas; Klanten, Robert; Ehmann, Sven; Hanschke, Verena; Sauter, Joachim (Berlin : Die Gestalten, 2011)
- Look: constructing visual performance and optical seduction##- Touch: examining intelligent interfaces and tactile communication##- Explore: discovering new terrains of speculation and innovation##- Engage: establishing operations of involvement and interaction##- Intervene: encouraging personal empowerment.
boek